A pilot study evaluating the contribution of fetal MRI to prenatal sonography for the diagnosis and management of congenital central nervous system (CNS) malformations. (18th April 2012) - Thomas, T; Ledingham, MA
Abstract : MRI for evaluating CNS anomalies detected on antenatal sonography has not become standard practice in our unit. This pilot study was carried out to determine the frequency at which MRI provides additional information in this setting. Going back from August 2010 a retrospective review of available case notes of 16 consecutive patients who attended our unit with fetal CNS abnormalities diagnosed on ultrasonography and then went on to have an MRI was done. The most common abnormality on sonography was ventriculomegaly (10 out the 16 cases) followed by cerebellar abnormality and suspected corpus callosum agenesis in 2 cases each. There was one case each of cortical cyst and megacisterna. Analysis of findings revealed that the MRI findings concurred with ultrasound findings in 10 of the 16 cases (62.5%) although additional information which did not influence counselling was obtained in 6 out of these 10 patients. In 6 of the 16 patients (37.5%) the MRI findings yielded information altered the counselling patients received. Magnetic resonance imaging findings not found by ultrasound included periventricular cavitation with subcortical white matter injury, agenesis of the corpus callosum, septum pellucidum agenesis, fine intraventricular adhesions suggestive of congenital CMV infection and cortical gyral abnormality. In conclusion when a CNS anomaly is detected by sonography, MRI findings might lead to altered diagnosis and patient counselling. Larger studies are needed to justify additional funding for fetal MRI examination to be made part of standard examination on sonographic diagnosis of a CNS abnormality.